Studies of Ancient Townscape Regeneration through the Articulation of the Space Syntax Methodology - Weilu Lv (Taylor & Francis Group, 2019)
In post-heritage-application times, the protection and development of the ancient towns in the Grand Canal areas have become an upmost priority. The current research is set in Keqiao ancient town. It works through the old map from Qing Dynasty, the maps that were drawn between the 1940s and the 1950s, as well as the electronic map gauged in 2013. Drawing on the quantitative analysis of space syntax, the research concludes that from the Qing Dynasty to date, the area with the highest integrated core area is the so-called “Three-Bridge-Four-Water” area. Using the connectivity value of the transformation proposal and the sample area of Shenjialou, this research confirms that enhancing the connection between the water system and the ancient town space would decrease the highest depth value and increase the integration value of Keqiao ancient town. The aim of this research is to study the feasibility of regenerating the vitality of Keqiao ancient town through refining the relationship between the water network system and the town space.